Immunohistochemical expression of CK20, CK7, and CDX2 in colorectal carcinoma in correlation with pathomorphological characteristics - Nevena Ilieva (Folia Medica, 2022)
Introduction: Colorectal carcinoma is the third most common cancer worldwide. The usual immunophenotype of colorectal adenocarcinoma is CDX2 positive, CK20 positive, and CK7 negative. Aberrant expression is reported in a variety of colorectal carcinomas but its relation to morphological variables and survival data is still unclear. Aim: The aim of this study was to investigate the correlation between the aberrant immunostaining of colorectal carcinoma and different clinicopathological characteristics. Materials and methods: Immunohistochemical expression of CK20, CK7, and CDX2 was evaluated in 71 cases of colorectal carcinoma. Statistical analysis was performed to identify correlations between the morphological characteristics and the immunoprofile of colorectal carcinoma. Results: Positive cytoplasmic and/or membranous signal for CK20 was observed in 66.2% of colorectal carcinomas. CK7 positive immunostaining was seen in 7% of the cases. In terms of combined expression of CK20 and CK7, the proportion of immunoprofile CK20+/CK7− was the highest, accounting for 46 out of 71 colorectal carcinomas, followed by CK20−/CK7−, then CK20−/CK7+ and CK20+/CK7+. Concerning CDX2, the majority of colorectal carcinomas (87.3%) showed positive staining. Statistically significant correlation was established between CDX2 expression and histologic grade and depth of tumour invasion. Loss of CK20 positivity was associated with higher histologic grade. No association between CK7 expression and histopathologic features was established. Conclusions: The results support the heterogeneity of colorectal cancer. Over 35% of the cases in this study showed deviations from the expected immunoprofile. This should be taken into consideration when diagnosing colorectal carcinoma in metastatic regions.